2003
DOI: 10.1097/01.asn.0000090744.88722.ff
|View full text |Cite
|
Sign up to set email alerts
|

Urea Restrains Aldosterone-Induced Development of Peanut Agglutinin–Binding on Embryonic Renal Collecting Duct Epithelia

Abstract: Abstract. Peanut agglutinin (PNA) represents a commonly used marker for ␤-type intercalated (IC) cells and their distribution in the corticomedullary course of the collecting duct (CD) in the mature rabbit kidney. It has been shown that aldosterone is able to generate Ͼ90% of PNA-binding cells in an embryonic CD epithelium in vitro. In adult kidney, a maximum of only 25% PNA-positive cells is found in the cortical segment of the CD, and PNA-binding completely disappears in the inner-medullary CD. Molecules tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Lack of immunolabel for mab Ki67 reveals in analogy to the adult kidney that the cells within the epithelium stop to divide after day 6 of perfusion culture and remain in the functional interphase (data not shown). As demonstrated in recent investigations the generation of a flat CD epithelium with 6 mm in diameter derived from renal CD ampulla cells appears as a reliable model to investigate basic cellbiological questions such as epithelial polarization, upregulation, modulation and maintenance of CD features [18,22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of immunolabel for mab Ki67 reveals in analogy to the adult kidney that the cells within the epithelium stop to divide after day 6 of perfusion culture and remain in the functional interphase (data not shown). As demonstrated in recent investigations the generation of a flat CD epithelium with 6 mm in diameter derived from renal CD ampulla cells appears as a reliable model to investigate basic cellbiological questions such as epithelial polarization, upregulation, modulation and maintenance of CD features [18,22].…”
Section: Resultsmentioning
confidence: 99%
“…1D). The holders were then placed for 24 hours in a 24-well plate in a CO 2 -incubator containing 5% CO 2 /95% air atmosphere [17,18]. During culture of the explants in Iscove´s Modified Dulbecco´s Medium (IMDM; order # 21980 -032; Gibco BRL Life Technologies, Eggenstein, Germany) including 10% fetal bovine serum (Boehringer, Mannheim, Germany) an outgrowth of cells from the CD ampullae was observed.…”
Section: Generation Of Flat CD Epithelia In Perfusion Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we found that embryonic renal tissue is a target for aldosterone, since it promotes the functional maturation of collecting duct epithelium [27]. Furthermore, we detected that aldosterone exerts a tubulogenic effect promoting the development of structured tubules derived from renal stem/progenitor cells [18][19][20].…”
Section: Discussionmentioning
confidence: 79%
“…23 In perfusion culture the cells of the CD ampulla have been shown to develop into a functional epithelium showing features of adult principal and intercalated cells. 17 It has been shown earlier that the development of embryonic collecting duct cells can be influenced by the application of aldosterone [24][25][26] as well as by urea 27 and increased electrolyte concentrations. 28 Astonishingly, the present experiments show that chronically decreasing oxygen partial pressure in a defined manner during culture can trigger similar changes in the differentiation profile of the embryonic epithelia.…”
Section: Discussionmentioning
confidence: 99%